Borehole cement sheath integrity - numerical simulation under reservoir conditions - Ramos, Ricardo M. (2017)
The most important function of the cement sheath is to provide zonal isolation in a production well. To achieve this objective, a hydraulic seal must be obtained between the casing and the cement, and between the cement and the formation. Throughout the life of a production well the cement sheath is subject to different reservoir conditions. Drilling, changes in pressure and temperature due to production, stimulation, and natural tectonic activity can lead to cement damage. Smaller chronic leakages due to defective well tubulars or damaged cement sheaths in the well cause a loss in the sustained casing pressure (SCP). Ensuring well integrity means to protect the environment against leakage along the well and to guarantee its producing potential. The tool presented in the current paper allows the cement engineer to simulate underground well conditions. After simulating the chosen scenario, various outputs can be combined in the overall analysis, including compression, traction, thermo-elasticity, and microannulus to help the cement engineer to analyze and design the proper cement to be used during the completion process.